Inisiasi Model Replikasi Child-Friendly Airport: Pemberdayaan Petugas Bandara Abdulrachman Saleh dalam Wisata Edukasi Penerbangan - Maulana Anifa Silvia; Lady Silk Moonlight; Faoyan Agus Furyanto; Ahmad Musadek; Anton Budiarto (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2026)
The potential of regional airports as living laboratories for child-friendly educational tourism is often constrained by the readiness of front-line service personnel. This community service initiative aimed to enhance the understanding and capacity of 34 operational staff at Abdulrachman Saleh Airport, Malang, in facilitating aviation educational tourism. Utilizing a Participatory Action Research approach, the program was conducted through socialization, child-friendly interaction simulations, and Focus Group Discussions (FGDs). Data were evaluated using a 4-point scale assessment and qualitative thematic analysis. Quantitative results demonstrated program success, with a total average score of 3.52 (Good category). Attendance achieved the highest score (3.85), while practical simulation scored the lowest (3.47) due to psychological barriers in shifting from a rigid work demeanor to a flexible attitude. In conclusion, the program successfully transformed staff into non-formal educational agents. Program sustainability requires written SOPs to integrate aviation safety protocols with children's tour routes.